METAMORPHIC ANALYSIS IN SONG LYRICS BATAK TOBA â€œAUT BOI NIANâ€ WRITTEN BY WERVIN PANGGABEAN - Simanjuntak, Marudut Bernadtua (Study Program of English Literature, 2021)
This study aims to analyze the metamorphic sentences contained in a folk song which is popular in Indonesia.